Colourism and law in the UK: a story of colonial indifference? - Naqvi, Zainab Batul (Frontiers in Sociology, 2025)
In this paper I explore legal and judicial responses toward skin tone and colourism in the UK. I argue that despite incidents involving colourism coming before the courts, there is no mention of this oppression in the legal framework. Colourism is invisible to the law and courts. “Colour” is included under the protected characteristic of “race” in the equalities and hate crime frameworks, but this is inadequate. This approach, I argue, reinforces the wider issue that the law is incapable of effectively addressing racism so measures to tackle colourism are even further beyond its scope. The law’s weaknesses here are emblematic of its indifference toward racially minoritised communities and their experiences. This colonial-inspired strategy of indifference is dismissive, dehumanising, and disdainful toward the vulnerable people and groups who are most affected by colourism.